Validez y confiabilidad de la Escala de Tipos de Cultura Organizacional (ETCO), en trabajadores de organizaciones públicas y privadas en México - Reyes Hernández, Javier (2025)
The aim of this study is to determine the validity and reliability of the Organizational Culture Types Scale (ETCO). For this purpose, a quantitative, non-experimental, crosssectional, and instrumental study was conducted. A non-probabilistic selection process was carried out with 418 subjects from both public and private companies in Mexico City. The results indicate that, by eliminating four out of the 92 items from its original version, the ETCO demonstrates adequate exploratory and confirmatory factorial validity, as well as high reliability. Furthermore, a comparative profile of organizational culture types is presented by type and size of companies and job level, which enables the support of organizational change and development strategies.